Microbes in your life. - Schneider, Leo.; Fluchere, Henri, 1914-1991 (New York, Harcourt, Brace & World, 1966)
A discussion of microbiology which includes information on algae, protozoa, fungi, harmful and helpful bacteria, viruses, and antibiotics.
Keywords: Microbiology -- Juvenile literature; Microbiology